GUTAS, Dimitri: Greek Thought, Arabic Culture. The Graeco-Arabic Translation Movement in Baghdad and Early ÿAbbásid Society. - Ramón Guerrero, Rafael (Anales del Seminario de Historia de la Filosofía, 1999)
Sin resumen